Preventing Unauthorized Use of Personal Data in Ghostbots Post-Mortem: An Access and Authorization Model for Digital Wills - Bödecker, Jasmin; Karla, Jürgen (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The rise of AI-driven technologies, such as ghostbots, has introduced new challenges in digital legacy management, particularly regarding post-mortem data usage. A digital will can adress this challenge. Following the Design Science Research Method, this research proposes a structured access control model that enables Testators to define clear permissions for data access, inheritance, and the creation of ghostbots. The model integrates predefined roles and conditional access policies to ensure the Testators wisches regarding post-mortem data usage are met. The model is assessed by using logical proof and scenario-based evaluation. The findings highlight the necessity of robust access control mechanisms to prevent unauthorized use of personal data to enable ethical AI practices. By addressing these issues, this study contributes to the broader discourse on digital inheritance and ghostbots and provides an access control model framework for managing post-mortem digital identities through a digital will.